Dynamics of the Scope of Rice Farming by Farmers' Groups in Increasing Productivity - Faqih, Ahmad Nazar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
One of the important parts of Indonesia's agricultural industry and the country's ability to meet the nutritional needs of its people is the cultivation of lowland rice. However, the productivity of lowland rice farming often faces obstacles such as limited resources (both financial and technological) and unpredictable market conditions (both in terms of price and production costs). This study aims to analyze how farmer groups expand the area of ​​lowland rice cultivation to increase production. This study uses a qualitative approach by relying on secondary sources, collecting data through document reviews, and analyzing the data to produce findings or confirm them. Based on these findings, farmer income is greatly influenced by the combination of fixed costs and variable costs that form the cost structure of the farm. The use of high-quality seeds, consistent control, and careful control of fertilizers and pesticides are components of an effective production strategy. Ownership of storage facilities and the use of post-harvest machinery are post-harvest tactics. Money and good seed quality are the two most important variables in crop yields. Managing expenses efficiently and diversifying income through non-farm activities are equally important. In short, the secret to the success of lowland rice farming is effective management, appropriate cultivation and post-harvest techniques, and maximum utilization of available resources. If they want to use modern techniques, they need help and education.